Moderation of the Narrative Discourse and Historical Authenticity in William Faulkner's ABSALOM, ABSALOM! - Mohammed, Marwan Kadhim; Farhan, Mohammed Deraa (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims to introduce Faulkner's concept of moderation in narrative discourse and its relationship to historical authenticity, to determine how this concept is embodied in the structure and the language of the novel. The study also aims to show how Faulkner's novel Absalom, Absalom! Reflects aspects of historical authenticity by employing the concept of moderation as a basis for balance in narrative discourse. Methods: Fisher and Ravizza's theory of responding to moderate reasons was chosen as the theoretical framework for the study. The descriptive analytical method was used to analyze selected texts from Faulkner’s novel Absalom, Absalom! to investigate how moderation and historical authenticity are embodied in the narrative discourse of that novel. The results obtained from the analysis were then compared with Fisher and Ravizza's theory to highlight the relationships between the concepts of moderation and historical authenticity and how each influences the other. Results: The concept of moderation is evident in highlighting important aspects of historical authenticity. The narrative discourse relies on historical authenticity as as a crucial foundation for achieving a balance, effectively influencing the portrayal of the concept of moderation. Faulkner's narrative discourse is closely associated with historical authenticity. Balance is achieved in the novel by embodying the concepts of moderation and historical authenticity. Conclusions: Faulkner reformulates the narrative discourse of the concept of moderation with historical authenticity that leads him to strengthen the spirit of tolerance as an essential component of the balance of that discourse.